TEACHING READING FOR YOUNG LEARNERS IN EFL CONTEXT - Lingga Agustina Suganda (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
Abstract: All young children are highly motivated to learn language. Millions of EFL children are learning reading as part of learning English, and thousands of EFL teachers are searching for an approach to teaching reading that will work most effectively. The concern of this paper is finding the effective way of teaching reading to young learners in EFL context. The content of children‟s literature can motivate the interest of students to learn a new language. Good, effective, and suitable approaches are for helping the students in their development. However, there is no one best approach to teaching reading, because one that works for one child may not work at all for another child. Good teachers have to recognize that children learn in different ways and require different strategies. Teachers need to draw on ideas from a number of different approaches and add ideas that come from their own experience. Therefore, the role of the parent or teacher in supporting reading progress is crucial. In conclusion, there are three important points for children reading success, namely: (1) innovative and suitable approach, (2) effective material, and (3) parents or teachers‟ role. All these three elements are critical in order to teach all kids to read.Keywords: Reading, young learners, approach, children’s literature, teachers and parents’ role.